Circular - Citrine, Walter, 1887-1983
1937-07-30 016b-0065-001 NATIONAL COUNCIL OF LABOUR TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1 TRADES UNION CONGRESS Secretary: SIR WALTER M. CITRINE (Victoria 9820) THE LABOUR PARTY Secretary: J.S. MIDDLETON (Victoria 8016) PARLIAMENTARY LABOUR PARTY Secretary: H. SCOTT LINDSAY (Whitehall 6240) Circ 119 July 30th, 1937. Dear Secretary, The National Council of Labour at its Meeting in London this week agreed to publish the enclosed Manifesto on the Spanish Revolt, and it has already received wide attention in the press. In addition, the Council had under consideration the possibility of the Government taking action in the direction of recognising General Franco after Parliament rises at the end of this week, and it issued the following: "The National Council of Labour views with alarm the attitude of the Government in relationship to the Spanish conflict. "We warn the nation that there is a grave danger that the Government will take advantage of the Holiday Season, and of Parliament being in recess, to recognise General Franco. "We urge the Party and the Movement and all lovers of Freedom to be on their guard and to take every step open to them to protest against any such action." It has been proposed by the I.F.T.U. and the L.S.I. that Propaganda Meetings on Spain should be held during the first week in August. It is recognised that during this period it may not be very easy for you to secure satisfactory meetings because of the occurrence of the Bank holiday; the National Council of Labour, therefore, recommends that Affiliated Organisations should use such opportunities throughout the month as they may feel are most useful for this purpose. It is also suggested that, apart from the possibility of holding early meetings on the lines proposed, the views of your Committee on this matter might be urgently conveyed by telegram or letter to the Secretary of State for Foreign Affairs at Whitehall. With kind regards, Yours very sincerely, W.M. Citrine. J.S.Middleton. 292/946/16b/71(i)